2019
DOI: 10.1016/j.conctc.2019.100321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of safety and immunogenicity of pentavalent DTP-HB-Hib vaccine administered by disposable-syringe jet injector in India

Abstract: Introduction We conducted a randomized, observer-blind, non-inferiority, parallel-group clinical study of diphtheria, tetanus, pertussis, hepatitis B, and Haemophilus influenzae type b conjugate (pentavalent) vaccination of infants in India. Goals were to determine whether the seropositivity rate after vaccination via disposable-syringe jet injector (DSJI) was non-inferior to that via needle and syringe (N-S), and to compare the safety of vaccination by the two methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
2
9
1
Order By: Relevance
“…In our study, 41.2% of the infants were immune against pertussis before vaccination (maternal immunity), which increased to 63.7% 1 month after the third dose of the vaccine. This result was similar to the study of (8). In the study of (15) 6 months after the third dose of the Pentavalent vaccine, 17.3% had pertussis immunity (15).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, 41.2% of the infants were immune against pertussis before vaccination (maternal immunity), which increased to 63.7% 1 month after the third dose of the vaccine. This result was similar to the study of (8). In the study of (15) 6 months after the third dose of the Pentavalent vaccine, 17.3% had pertussis immunity (15).…”
Section: Discussionsupporting
confidence: 85%
“…The first combination vaccine was used in children in 1940 (6). Five antigens are currently available as a Pentavalent combination vaccine for protection against tuberculosis, diphtheria, tetanus, whooping cough, poliomyelitis, and measles, as well as HepB and Hib in the national immunization program in developing countries (7,8). According to the WHO, vaccines are one of the most powerful tools in public health and more children are now being immunized than ever before (9).…”
Section: Introductionmentioning
confidence: 99%
“…The Pharmajet Stratis, a disposable-syringe jet injector, has been assessed in a clinical trial (NCT02253407) in India. It was shown that similar levels of seroconversion were observed after measles, mumps, and rubella (MMR) vaccination by jet injector as with needle and syringe injection in 170 toddlers 35 days post-injection, as well as similar adverse effect rates [ 178 ]. However, another trial (NCT02409095) in India with the same disposable-syringe jet injector but for DTP-HB-Hib vaccination had to be prematurely terminated after a higher frequency of injection site reaction was observed in those treated with the jet injector compared to those injected by needle and syringe.…”
Section: Vaccination Into the Dermal Compartment Without Needle Anmentioning
confidence: 99%
“…In this context, in addition to microneedle-based technology previously exposed, some needle-free systems also aimed at solving these problems were developed. Needle-free jet injectors are currently one of the effective alternatives to conventional needle injections, with multiple commercial devices cited in clinical trials ( Bremseth and Pass, 2001 ; Yousafzai et al, 2017 ; Bavdekar et al, 2019 ). TDD based on this mechanism entails ejection of a liquid drug through a fine nozzle at elevated pressure, thus generating a narrow super-fast fluid jet easily penetrable into the skin and tissue ( Figure 12 ).…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%